Congenital pancreas malformations: a clinical case report - Bento, A (2013)
OBJECTIVE: This study aimed to review the congenital malformation known as agenesis of the dorsal pancreas (ADP) and other pancreatic birth defects, based on a rare and exemplary clinical case of pancreatic malformations. The intent was to review the latest information published in the national and international literature on pancreatic birth defects, and to investigate the diversity of clinical presentations of ADP and other congenital pancreas abnormalities. The purpose was to identify which situations have therapeutic indication, the most appropriate time to institute treatment, and the currently available medical or surgical treatment of pancreatic congenital malformations. RESULTS: ADP is a very rare malformation that occurs during organogenesis. In the last decades, a large volume of embryological and genetic information has been obtained, helping to understand the causes of pancreatic malformations, which must be studied and understood as a whole. CONCLUSION: Pancreatic malformations are infrequently studied causes of acute and chronic pancreatic in adults. The possibility of pancreatic malformations should always be considered in patients with acute or chronic pancreatitis with no evident cause.